Deteksi Resistensi Piretroid Secara Bioassay dan Mutasi Gen kdr pada Aedes aegypti dan Aedes albopictus - Puti Reno Diandra K.; Hasmiwati Hasmiwati; Beni Indra; Selfi Renita Rusjdi; Wirsma Arif Harahap; Nice Rachmawati Masnadi (Majalah Kedokteran Andalas, 2023)
Objective: The aim of this study is to detect the insecticide resistance by bioassay test and to detect the kdr mutation in Aedes aegypti and Aedes albopictus.Methods: This study was a narrative review that evaluated various articles related to detection of pyrethroid resistance by bioassay and mutation of the kdr gene in Ae. aegypti and Ae. albopictus sourced from PubMed, Google Scholar, and ProQuest database.Results: The results of the study review show that almost the entire population of Ae. aegypti and Ae. albopictus is already resistant to pyrethroid insecticide based on the bioassay detection using the WHO Susceptibility Test and CDC Bottle Assay protocols, and several variations of the kdr gene allele have been found, especially the V1016G, F1534C, and S989P genesConclusion: Ae. aegypti is resistant to pyrethroid insecticides, especially to deltamethrin and permethrin groups, Ae. albopictus are generally still in the susceptible status, and mutations in kdr gene are mostly found in the population of Ae. aegypti. The genotypes of the kdr that experienced many mutations are V1016G, F1534C, and S989P.